2012
DOI: 10.1242/jcs.106682
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia causes triglyceride accumulation via HIF-1-mediated stimulation of lipin 1 expression

Abstract: SummaryAdaptation to hypoxia involves hypoxia-inducible transcription factors (HIFs) and requires reprogramming of cellular metabolism that is essential during both physiological and pathological processes. In contrast to the established role of HIF-1 in glucose metabolism, the involvement of HIFs and the molecular mechanisms concerning the effects of hypoxia on lipid metabolism are poorly characterized. Here, we report that exposure of human cells to hypoxia causes accumulation of triglycerides and lipid drop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
130
1
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 125 publications
(144 citation statements)
references
References 49 publications
9
130
1
4
Order By: Relevance
“…Adaptation to hypoxia involves metabolic reprogramming driven by upregulation of the HIF-1-target genes that stimulate uptake of glucose, glycolysis, lactate production and secretion, glycogen storage and glutamine catabolism (Brahimi-Horn et al, 2011), and promote accumulation of triglycerides in lipid droplets (Kourti et al, 2015;Mylonis et al, 2012) as well as, in contrast, repressing mitochondrial metabolism and oxidative phosphorylation (Semenza, 2011). To ensure cell survival under hypoxia, HIF-1 also stimulates mitochondrial autophagy and upregulates the expression of anti-apoptotic genes of the Bcl-2 family (Sendoel and Hengartner, 2014), thereby also increasing resistance of cancer cells to chemotherapy (Wilson and Hay, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Adaptation to hypoxia involves metabolic reprogramming driven by upregulation of the HIF-1-target genes that stimulate uptake of glucose, glycolysis, lactate production and secretion, glycogen storage and glutamine catabolism (Brahimi-Horn et al, 2011), and promote accumulation of triglycerides in lipid droplets (Kourti et al, 2015;Mylonis et al, 2012) as well as, in contrast, repressing mitochondrial metabolism and oxidative phosphorylation (Semenza, 2011). To ensure cell survival under hypoxia, HIF-1 also stimulates mitochondrial autophagy and upregulates the expression of anti-apoptotic genes of the Bcl-2 family (Sendoel and Hengartner, 2014), thereby also increasing resistance of cancer cells to chemotherapy (Wilson and Hay, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The excess lipid will, in turn, be used to form triglyceride and lipid droplets for storage. In this process, HIF-1a directly regulates phosphatidate phosphatase isoform 1 (Lipin1), an essential enzymes that catalyzes triglyceride biosynthesis in the penultimate step, and hypoxia-inducible protein 2 (HIG2) which functions in lipid droplets accumulation on membranes [32,33]. Overall, these results showed that hypoxia can enhance fatty acid synthesis and triglyceride storage through an HIF-1a-dependent pathway in cancer cells.…”
Section: Hif-1 and Lipid Metabolism In Cancer Cellsmentioning
confidence: 86%
“…15 It has been shown that HIF-mediated stimulation of lipin 1 expression causes triglyceride accumulation. 23 Furthermore, glycogen synthesis is induced in hypoxia by HIF-1 and promotes tumor cell survival. 24 This phenomenon can sometimes mimic a signet ring cell carcinoma 15 ( Figure 2, E).…”
Section: Pancreatic Neuroendocrine Proliferationsmentioning
confidence: 99%